Development of a web portal to forecast the monthly mean chlorophyll concentration of the waters off Peninsular Malaysia's west coast - Gopal, Kathiresan; Shitan, Mahendran (Institute for Mathematical Research, Universiti Putra Malaysia, 2018)
The principal photosynthetic pigment of chlorophyll (chl-a) in the water is produced by phytoplankton and its concentration (CC) is the biomass and abundance indicator of phytoplankton. The small pelagic fishes which feed on phytoplankton is one of the dominant groups caught in Malaysia. The typical challenge in fisheries is to identify a fruitful fishing ground at any given time. Based on the relationship amongst CC, phytoplankton and food chain of pelagic fishes, it can be suggested that waters with high levels of CC may indicate a more favourable fishing ground. Thus, using CC may help to narrow down the fishing ground search and would be useful to fishermen. This paper described the development of a web portal to forecast the monthly mean CC of the waters off Peninsular Malaysia’s west coast. The portal’s functionality was illustrated with time series modelling and forecasting of 3 fisheries sites using Holt-Winters seasonal additive model. The portal consists of forecast outputs as well as related information and is primarily intended for use as a tool for fishermen with the advantage of easy accessibility.